Do Published Cooking Temperatures Correspond with Consumer and Chef Perceptions of Steak Degrees of Doneness? - Brittany A. Olson; Emily A Rice; Jessie Vipham; John M. Gonzalez; Lauren L. Prill; Lindsey N. Drey; Michael Colle; Michael D. Chao; Phillip Bass; Travis O'Quinn (Meat and Muscle Biology, 2019)
The objective of this study was to assess consumer and chef perceptions and knowledge of beef degrees of doneness (DOD) as well as to measure the changes in cooked color over time related to DOD. Steaks from strip loins (M. longissimus lumborum) from each of 5 quality treatments were used for this study. Steaks were cooked to an endpoint temperature of either very-rare (54°C), rare (60°C), medium-rare (63°C), medium (71°C), well-done (77°C), or very well-done (82°C). L*, a*, and b* were evaluated at 0, 1, 2, 3, 6, 9, and 12 min post-cutting and digital pictures were taken immediately on an internal surface of the steak. Digital surveys for the evaluation of the images of the cooked steaks were created for consumers and chefs. There were time × DOD interactions (P < 0.05) for L*, a*, and b* values. For very-rare, rare, medium-rare, and medium, a* values increased (P < 0.05) over time. For L*, well-done and very well-done steaks became darker (P < 0.05) and very-rare, rare, and medium-rare steaks became lighter (P < 0.05) over time. Surveys indicated consumers determine DOD when cooking beef in their home primarily by using color, whereas chefs primarily use touch to determine DOD. There were no quality grade effects (P > 0.05) for DOD responses for steak pictures evaluated by consumers or chefs. Consumers identified the DOD of cooked steaks as the DOD that corresponds to published end-point temperatures 27 to 35% of the time. Chefs typically identified the DOD as 1 DOD higher than which the steaks were cooked for steaks cooked to medium or less and 1 DOD lower for steaks cooked to well-done and higher. This indicates differences exist in the perceptions of DOD between culinary professionals and consumers, and may contribute to decreased consumer satisfaction when ordering steaks in a restaurant.